Interictal plasma glutamate levels are elevated in individuals with episodic and chronic migraine - Chae Gyu Park; Min Kyung Chu (Scientific Reports, 2022)
Abstract Glutamate is implicated in migraine pathogenesis including central sensitization and pain transmission. Altered plasma glutamate levels has been noted in migraine. Chronic migraine (CM) presented a higher degree of central sensitization and pain transmission than episodic migraine (EM). However, no study has evaluated plasma glutamate levels separately in EM and CM. This study aimed to assess plasma glutamate levels in EM and CM compared to controls. An enzyme-linked immunosorbent assay was used to assess plasma glutamate levels in females with EM (n = 98) and CM (n = 92) as well as controls (n = 50). Plasma glutamate levels in participants with EM (median and interquartile range, 49.73 [40.82–66.12] μmol/L, p < 0.001) and CM (58.70 [44.64–72.46] μmol/L, p < 0.001) were significantly higher than those in controls (38.79 [29.50–53.60] μmol/L). Glutamate levels were not significantly different between participants with EM and CM (p = 0.075). There was no significant association of plasma glutamate levels with headache frequency (exponential and 95% confidence interval, 1.285 [0.941–1.755]) and intensity (mild, 59.95 [59.95–59.95] μmol/L vs. moderate, 52.76 [40.83–106.89] μmol/L vs. severe, 55.16 [42.34–68.03] μmol/L, p = 0.472). The plasma glutamate level is a potential indicator for EM and CM.